MODELING OF PARTIAL OXIDATION OF METHANE IN A MEMBRANE REACTOR - Fernandes, F. A. N.; Souza, C. P.; Sousa, J. F. (Revista de Engenharia Térmica, 2006)
Partial oxidation of methane is one of the most important chemical processes for the production of syngas. In recent years, the abundant availability of natural gas and the increasing demand of hydrogen have led to high interest to further develop this process increasing the yield of syngas. In this work the partial oxidation of methane was studied from a modeling point of view in a membrane reactor and in a conventional reactor. A mathematical model of a membrane reactor used for partial oxidation of methane, assuming steadystate conditions, was developed to simulate and compare the maximum yields and operating conditions in the reactor with that in a conventional reactor. Simulation results show that different parameters affect methane conversion and H /CO ratio, such as temperature, operating conditions, and membrane 2 parameters such as membrane permeance. In a membrane reactor an increase in the operating pressure corresponds to an increase in methane conversion, since allows for a greater partial pressure gradient between the reaction and permeate zone, thus contributing to shift the equilibrium towards the products. As such, the membrane reactors are a good alternative to produce syngas especially for GTL processes. Operating conditions can be set to control the H2/CO ratio to a desired value, and high conversions at mild temperatures can be achieved reducing capital and operational costs.